Applications of Artificial Intelligence-Assisted Computing in “Piano Education” - Song, Xiaoduo; Phokha , Pramote (Journal of Ecohumanism, 2024)
Introduction: The field of music is benefiting from the promotion and implementation of contemporary machine technology and information technologies due to the continuous developments in this industry. Artificial Intelligence (AI) is a popular and highly demanding science and technology that offers a broad range of approaches, ideas, and technical assistance. Artificial intelligence technologies have substantially enhanced learning and instruction, training, music applications, intelligent devices, etc. in the music education sector by giving new life to educational endeavours. Methods: Education department have shown the most effective use of technological innovations in their methods of instruction and learning when compared to other organisations. For educators and learners in distant locations, Instruction and Education (TaL) using music and musical devices may be very difficult. TaL of playing the piano is taken advantage of in this research project by using the Musical Instrument Digital Interface (MIDI) and Acoustic Editing for Synchronisation Tracks and Organising (MAESTRO) dataset. Results: The result includes virtual recordings of recording piano performances with labels and audio waveforms. Artificial Intellect (AI) is used to apply the Multimodal Signals Classifier (MSC) approach to a dataset in order to give learners intelligent assistance during their educational experience. This MSC methodology is used on Wi-Fi Networks (WN) to classify signals after gathering and updating the collected data. Conclusion: This paper represents a new effort in the field of artificial intelligence, hoping to help piano students in a timely manner by solving some challenging piano practice problems using cutting-edge neural networks, in addition to using big data technologies for teaching assistance. Identify and fix any rhythmic and fingering problems in your performance. Through the use of artificial intelligence technology, it is examined, processed, and provides guidance for piano practice, enabling practitioners to more precisely address practice-related issues and increase practice efficiency.